2016
DOI: 10.1096/fj.201600616r
|View full text |Cite
|
Sign up to set email alerts
|

Ticagrelor regulates osteoblast and osteoclast function and promotes bone formation in vivo via an adenosine‐dependent mechanism

Abstract: As many as 10% of bone fractures heal poorly, and large bone defects resulting from trauma, tumor, or infection may not heal without surgical intervention. Activation of adenosine A receptors (ARs) stimulates bone formation. Ticagrelor and dipyridamole inhibit platelet function by inhibiting P2Y receptors and platelet phosphodiesterase, respectively, but share the capacity to inhibit cellular uptake of adenosine and thereby increase extracellular adenosine levels. Because dipyridamole promotes bone regeneratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 54 publications
4
58
0
1
Order By: Relevance
“…DIPY is a well‐known anti‐thrombotic agent and recently it has been investigated for its osteogenic potential via adenosine receptor ligation. Activation of the adenosine A 2A receptor has demonstrated the ability to attenuate osteoclast differentiation and upregulate osteoblast differentiation . DIPY‐induced A 2A R ligation has been reported to augment critical bone defect healing to a similar degree as BMP‐2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DIPY is a well‐known anti‐thrombotic agent and recently it has been investigated for its osteogenic potential via adenosine receptor ligation. Activation of the adenosine A 2A receptor has demonstrated the ability to attenuate osteoclast differentiation and upregulate osteoblast differentiation . DIPY‐induced A 2A R ligation has been reported to augment critical bone defect healing to a similar degree as BMP‐2.…”
Section: Discussionmentioning
confidence: 99%
“…Data collected from studies both in vitro and in vivo have also demonstrated that osteoblast activity is positively modulated by A 2A R ligation; in vivo work has demonstrated adenosine‐stimulated osteogenesis regenerative potential in murine calvarial models . Calvarial defects replaced with 3D‐printed scaffolds coated with A 2A R agonists healed bone as effectively as rhBMP‐2, without the unpredictability and expense that have been previously associated with rhBMPs. More recently, our group has demonstrated that these principles have shown translational promise in large animal calvarial defects, with the adenosine A 2A R indirect agonist dipyridamole (DIPY) exerting a significant effect on bone regenerative capacity.…”
mentioning
confidence: 99%
“…Many bioactive agents have been assessed as potential bone regenerative therapeutics. Among these molecules, those that activate purinergic receptors have recently been reported to have significant therapeutic potential without undesired side effects that often accompany other notable compounds such as recombinant human bone morphogenetic protein (rhBMP-2) (Bekisz et al, 2017;Costa et al, 2011;Mediero & Cronstein, 2013;Mediero, Wilder, Perez-Aso, & Cronstein, 2015;Mediero, Frenkel et al, 2012;Mediero et al, 2016).…”
Section: Adenosine Receptor Activationmentioning
confidence: 99%
“…These findings point to the possible therapeutic role of targeting Netrin-1 in overactive osteoclast diseases. As such, antibody-mediated blockade of Netrin-1 and Unc5b, but not DCC, reduced paw inflammation, bone erosion and osteoclast numbers in a mouse model of inflammatory arthritis [71]. …”
Section: - the Role Of Netrins And Semaphorins In Innate Immunitymentioning
confidence: 99%